PENINGKATAN PERAN FORUM KEMITRAAN POLISI MASYARAKAT (FKPM) DALAM PENCEGAHAN TINDAK PIDANA - Andayani, Tri Wahyu (De Jure: Jurnal Hukum dan Syari'ah, 2014)
The purpose of  this paper is to  improve  role  of police  community  partnership forum (FKPM)  in  the prevention of crime. Methodology approach  in this study uses an empirical- juridical approach, because the scope of the research is to study law in  action. A prevention effort of criminal act not only as police responsibility but also as society responsibility entirely. To develop a partnership between police and society, it is formed community policing model (Perpolisian Masyarakat/ Polmas) as regulated in Decree  of  Indonesia Chief Police  No.  Skep/737/X/2005 on  Policies  and Implementation  Strategy  of  Community Policing Model  in  Police  Duties. In other words, Indonesia police move or empowering the people (pemberdayaan masyarakat) in order to  motivate the rising power of  the people themselves for performing functions of the police. Idea of alternative police also can be called as an attempt for empowering the society to create security function in their surroundings.